Career paths and university education: factors that determine the employment status of university graduates - Portocarrero Ramos, Heily Consepción; Campos Trigoso, Jonathan Alberto; Cruz Caro, Omer; Reina Marín, Yuri; Maicelo Guevara, Jorge Luis; Sánchez Bardales, Einstein; Chávez Santos, River (Frontiers in Education, 2025)
Employment outcomes are more strongly associated with specific career paths than with academic performance. Despite expanding university access, significant gaps persist between the training received and labor market conditions. The objective was to identify and analyze the factors that influence the employment situation of university graduates. A quantitative explanatory approach was used, with a sample of 3,009 graduates. A structured survey was administered, and the data were analyzed using Logistic regression, Lasso regression, and Random Forest models. The results show that the variables with the greatest predictive power are the type of contract, time spent working, and income level. In contrast, academic variables such as GPA and theoretical or practical training showed little relevance. In comparison, employability is more associated with specific career paths than academic merits. The study reveals important findings for universities to strengthen applied training, encourage early entry into the workforce, and develop monitoring systems that allow them to adapt their educational offerings to the real demands of the professional environment. Understanding the factors that influence graduate employability is crucial to enhancing the significance of education and improving professional opportunities.